PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. VIRTUS FACILITY SERVICE UNIT KERJA PONDOK INDAH RESIDENCE JAKARTA SELATAN - Dimas Dwi Saputra; Agustina Mogi (Journal of Research and Publication Innovation, 2025)
Employee performance at PT. Virtus Facility Service Pondok Indah Residence work unit. This research aims to determine the influence of motivation and work discipline on employee performance at PT Virtus Facility Service Pondok Indah Residence work unit. This type of research is quantitative. The analytical methods used in this research are validity test, reliability test, classical assumption test, descriptive analysis, simple linear regression test, multiple linear regression test, correlation coefficient test, coefficient of determination test, t test and F test. The population in this study is Employees of PT Virtus Facility Service, Pondok Indah Residence work unit, used a saturated sample of 60 respondents. The results of this research based on the coefficient of determination show that motivation and work discipline have a contribution to employee performance of 0.360 or 36% while the remaining 64% is another variable that was not studied. The research results show the multiple linear regression equation Y = 16.164 + 0.255 X1 + 0.764 X2. The correlation coefficient value of Motivation (X1) to Performance (Y) is 0.461, meaning the two variables have a low level of relationship, the coefficient value of work discipline (X2) to Performance (Y) is 0.592, meaning the two variables have a low level of relationship. The results of testing the simultaneous influence of the independent variable on the dependent variable obtained a calculated F value = 16.027 > F table value = 3.16, so it can be concluded that partially or simultaneously there is an influence between Motivation and Work Discipline on the Performance of PT Employees. Virtus Facility Service Pondok Indah Residence work unit